(untitled) (International Journal of Environmental Sciences, 2025)
Knowledge in any form is crucial in daily tasks. Everyone is familiar with how to perform their job, and this expertise can later be applied to similar activities by adjusting it to new contexts based on experience. Contemporary knowledge-centric perspectives on organisations suggest that knowledge keeps organizations unified. Nowadays, knowledge is increasingly regarded as the most valuable asset for organisations, and it is believed that every experience can be leveraged and reused. This applies not only to specific areas like coding but also implies that any form of knowledge can be utilized by others. "Recognising, overseeing, and sharing knowledge while implementing best practices has benefited some companies, often saving or generating vast amounts of money". The 2030 Agenda for Sustainable Development, which was adopted by all UN Member States in 2015, offers a collective framework aimed at ensuring peace and prosperity for individuals and the planet, both now and in the future. Central to this agenda are the 17 Sustainable Development Goals (SDGs), which represent an urgent call to action for every country, regardless of its development status, in a collaborative global initiative. These goals emphasise that efforts to eliminate poverty and other forms of deprivation should be pursued alongside strategies that enhance health and education, decrease inequality, and encourage economic growth, all while addressing climate change and striving to safeguard our oceans and forests. The present study addresses the role of SDG embedded management education with special attention to creating a knowledge economy which may cater to industry-fit employable graduates.